Histological, immunohistochemical assessment and DNA fingerprint species identification of some meat products in Egypt - Heba F. Kamaly; Abeer M. Hassan; Zainab MA Youssef; Fatma El-Zahraa Ahmed Mustafa (Scientific Reports)
Abstract A total of sixty commercial beef products, represented by minced meat, sausage, kofta, and burger, with fifteen samples per product, were collected randomly from different markets in Assiut city, Egypt. Samples were examined histologically, immunohistochemically and molecularly to investigate tissue composition and species substitution. Polymerase Chain Reaction (PCR) was applied to confirm the beef origin of different marketed beef products and determine if there are any adulteration and/or contamination with rodents and canine species. The histological investigation finds significant differences in skeletal muscle content, with the highest proportion in minced meat, whereas the lowest detected in kofta. Several animal tissues were detected, including adipose tissue, collagen, cartilage, and bone, where kofta showed the highest levels. We also detected plant tissues, predominantly found in burger samples. Expression Bcl2 indicated the maximum intensity in sausage, while burger showed the lowest expression. PCR results revealed that 89.13% were pure beef products, 10.87% were with rat meat contamination, and 100% of examined samples were negative for canine species. These results highlight the efficacy of histology, Bcl2 immunohistochemistry and PCR in assessing meat quality and distinguishing adulteration.